Impact of material composition and food waste decomposition on characteristics of fuel briquettes - Nikiema, Josiane; Asamoah, Bernice; Egblewogbe, M. N. Y. H.; Akomea-Agyin, J.; Cofie, Olufunke O.; Hughes, A.F.; Gebreyesus, G.; Asiedu, Kerewaa Zipporah; Njenga, M. (Elsevier, 2022)
This study investigated the potential of using locally available municipal solid wastes (MSW) (such as food wastes from restaurants, charcoal dust, coconut husk and shell, and sawdust) as feedstock to produce noncarbonized fuel briquettes. A low-cost briquetting machine sourced from Alfaster Industries in Kenya served to demonstrate the concept. Using decomposed food waste resulted in briquettes with higher bulk density (+4%), greater net calorific value (+18%) and lower burning rate (-24%), compared to the use of regular food waste. There was no significant difference in ash content from the two briquette types. The results also indicate that decomposing food waste and mixing it with tree-based raw materials such as coconut waste, charcoal waste or sawdust improves the quality of briquettes, and enhances the temperatures achieved during combustion. This recycling solution has the potential to serve multiple benefits in MSW management for sustainable cities while reducing rural land degradation and deforestation.